Review paperMulti-catheter interstitial accelerated partial breast irradiation – tips and tricks for a good insertion - Tang, Johann I.; Tan, Poh Wee; Yanling Koh, Vicky; Buhari, Shaik Ahmad (Journal of Contemporary Brachytherapy, 2014)
Adjuvant radiotherapy is recommended post breast conserving surgery. Accelerated Partial Breast Irradiation (APBI) offers a more attractive shorter course of treatment over 5 days compared to standard conventional external beam radiotherapy, which is often protracted. Multi-catheter interstitial APBI offers excellent dosimetric coverage. This article describes two insertion techniques for multi-catheter interstitial APBI, the operator dependent freehand technique, and the easier to learn template technique. The indications, benefits, and drawbacks of these two techniques are discussed.